2001
DOI: 10.1037/0735-7036.115.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of signs by dolphins (Tursiops truncatus).

Abstract: The authors assessed the ability of 6 captive dolphins (Tursiops truncatus) to comprehend without explicit training 3 human communicative signs (pointing, directed gaze, and replica). Pointing consisted of indicating the target item with the index finger and a fully extended arm. Directed gaze consisted of orienting the head and eyes toward the target item while the rest of the body remained stationary. The replica signal consisted of holding up an exact duplicate of the target item. On the initial series of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 24 publications
4
69
1
Order By: Relevance
“…However, this hypothesis has been countered by other findings: human-socialized undomesticated individuals, such as wolves (Canis lupus; Udell, Dorey, & Wynne, 2008;Udell, Spencer, Dorey, & Wynne, 2012), African elephants (Loxodonta africana; Smet & Byrne, 2013), dolphins (Tursiops truncatus; Pack & Herman, 2004, 2007Tschudin, Call, Dunbar, Harris, & van der Elst, 2001), fur seals (Arctocephalus pusillus, Schuemann & Call, 2004) and a gray seal (Halichoerus grypus, Shapiro, Janik, & Slater, 2003) have also been shown to be very successful, some not far from a dog's level of performance. Great apes are generally unskillful (e.g., see Povinelli, Reaux, Bierschwale, Allain, & Simon, 1997), but recently Lyn, Russel, and Hopkins (2010) showed that chimpanzees and bonobos raised in socio-linguistically rich environments perform much better than chimpanzees raised in standard laboratory housing.…”
Section: Introductionmentioning
confidence: 68%
“…However, this hypothesis has been countered by other findings: human-socialized undomesticated individuals, such as wolves (Canis lupus; Udell, Dorey, & Wynne, 2008;Udell, Spencer, Dorey, & Wynne, 2012), African elephants (Loxodonta africana; Smet & Byrne, 2013), dolphins (Tursiops truncatus; Pack & Herman, 2004, 2007Tschudin, Call, Dunbar, Harris, & van der Elst, 2001), fur seals (Arctocephalus pusillus, Schuemann & Call, 2004) and a gray seal (Halichoerus grypus, Shapiro, Janik, & Slater, 2003) have also been shown to be very successful, some not far from a dog's level of performance. Great apes are generally unskillful (e.g., see Povinelli, Reaux, Bierschwale, Allain, & Simon, 1997), but recently Lyn, Russel, and Hopkins (2010) showed that chimpanzees and bonobos raised in socio-linguistically rich environments perform much better than chimpanzees raised in standard laboratory housing.…”
Section: Introductionmentioning
confidence: 68%
“…Also, dolphins (Tursiops truncatus; Tschudin, Call, Dunbar, Harris, & van der Elst, 2001) and South African fur seals (Arctocephalus pusillus; Scheumann & Call, 2004) follow gaze in object-choice situations. Although there was no evidence that dogs (Canis familiaris) follow human gaze outside of a simulated foraging context into free space , they are very skillful in using human gaze in object-choice situations .…”
Section: Discussionmentioning
confidence: 99%
“…head and eye direction (Byrne & Whiten 1988;Tomasello & Call 1997)). The ability to follow gaze direction has recently been shown for a number of primates (see review in Emery 2000) and other social mammals such as dogs, Canis familiaris (Miklósi et al 1998), dolphins, Tursiops truncates (Tschudin et al 2001), and goats, Capra hircus (Kaminski et al 2001). Studies follow different paradigms that require individuals either: (i) to visually co-orient with a conspecific and/or human experimenter for tracking locations above, behind or to the side of them (e.g.…”
Section: Introductionmentioning
confidence: 99%